2021
DOI: 10.1021/acsanm.1c00828
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Edge-Induced Atomic-Scale Structural Phase Transitions of MoS2 Nanocrystals: Implications for a High-Performance Catalyst

Abstract: Molybdenum disulfide (MoS2) has attracted much attention as a material to replace the noble-metal-based hydrogen evolution reaction catalyst. Polymorphism is an important factor in improving the catalytic performance of transition-metal dichalcogenides (TMDs) including MoS2. Several methods have been proposed to synthesize the 1T/1T′ phase with high catalytic efficiency, and a gas–solid reaction has recently been proposed as one of the alternative methods. However, the atomic-scale reaction mechanism between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 48 publications
4
8
0
Order By: Relevance
“…To understand the atomistic reaction behavior in anion extraction-based polymorph conversion, DFT calculations for the reaction barriers of CO-mediated V S formation and S diffusion for polymorph conversion of WS 2 were conducted in the same process as the mechanism that was presented in the previous work. 43 The calculation results showed that the reaction barrier for the CO-mediated polymorph conversion of WS 2 was higher than that of MoS 2 , and the difference in reaction barriers was consistent with the experimental results. We modeled WS 2 nanocrystals with a triangular shape, which was observed in several previous reports.…”
supporting
confidence: 81%
See 4 more Smart Citations
“…To understand the atomistic reaction behavior in anion extraction-based polymorph conversion, DFT calculations for the reaction barriers of CO-mediated V S formation and S diffusion for polymorph conversion of WS 2 were conducted in the same process as the mechanism that was presented in the previous work. 43 The calculation results showed that the reaction barrier for the CO-mediated polymorph conversion of WS 2 was higher than that of MoS 2 , and the difference in reaction barriers was consistent with the experimental results. We modeled WS 2 nanocrystals with a triangular shape, which was observed in several previous reports.…”
supporting
confidence: 81%
“…Through the repeated diffusion of S atoms at the trigonal prismatic site to the octahedral site, the whole nanocrystal could be changed to the T phase, as suggested in a previous study. 43 Figure 5a shows a higher reaction barrier for the ratelimiting step (1.31 eV) than that of MoS 2 (0.49 eV). 43 Therefore, S diffusion to the octahedral site in WS 2 needs to overcome a higher reaction barrier than that in MoS 2 .…”
mentioning
confidence: 89%
See 3 more Smart Citations